Gambaran Perilaku Phubbing pada Mahasiswa Keperawatan UNSOED di Masa Endemi COVID-19 - Wiguna, Ilham; Awaludin, Sidik; Mulyaningrat, Wahyudi (Jurnal Keperawatan Klinis dan Komunitas (Clinical and Community Nursing Journal), 2024)
Background: Phubbing is a behaviour when a person keeps staring at the cell phone during social interactions, thus ignoring the interlocutor or speaking opponent. This behavior obviously disturb interpersonal relationship and may hurt other people feeling. While phubbing behavior is quite common among college students, it becomes interesting to explore. Objective: To describe phubbing behavior among UNSOED Nursing students during the COVID-19 endemic.Method: The research was descriptive with cross-sectional approach. This involved UNSOED Nursing students as respondents, with a sample of 203  which were chosen using the proportionate stratified random sampling technique. The instruments was Phubbing Scale, which consisted of two factors: communication disorders and obsession with cell phones. Data were analyzed using univariate methods.Results: Most of the respondents (91%) were women with a median age of 20 years old. Most of the respondents showed moderate behavior phubbing (87%), but 13% showed high phubbing behavior. For the dimensions of communication disorders and the greatest obsession with cell phones, the majority of respondents were at moderate level, with 91% and 65% consecutively.Conclusion: Phubbing behavior among UNSOED nursing students are at moderate level. Attention is needed toward cellphone usage to maintain caring practice among nursing students.INTISARILatar belakang: Phubbing adalah praktik melihat layar ponsel saat berinteraksi sosial sehingga mengabaikan lawan bicara. Perilaku ini dapat mengganggu hubungan antar manusia dan menyakiti perasaan orang lain. Kecenderungan perilaku phubbing banyak ditemukan pada mahasiswa sehingga menjadi fenomena yang menarik untuk diteliti. Tujuan: Penelitian ini bertujuan untuk melihat bagaimana gambaran perilaku phubbing mahasiswa Keperawatan UNSOED selama endemi COVID-19.Metode: Penelitian deskriptif cross-sectional ini melibatkan mahasiswa Keperawatan UNSOED, dengan sampel 203 responden menggunakan teknik proportionate stratified random-sampling. Instrumen yang digunakan adalah The Phubbing Scale yang terdiri dari dua faktor, gangguan komunikasi dan obsesi terhadap ponsel. Data dianalisis dengan metode univariat.Hasil: Sebagian besar  responden (91%) perempuan dengan nilai tengah usia 20 tahun. Sebagian besar responden menunjukkan perilaku phubbing sedang (87%), tetapi sebanyak 13% menunjukkan perilaku phubbing tinggi. Pada dimensi gangguan komunikasi dan obsesi terbesar terhadap ponsel mayoritas responden berada pada tingkat sedang (91% dan 65%).Simpulan: Perilaku phubbing mahasiswa keperawatan UNSOED berada pada tingkat sedang. Diperlukan pengawasan terhadap penggunaan ponsel agar penerapan konsep caring dapat dilaksanakan secara konsisten.